Electronic catalog as an object of quality assessment - G. A. Skaruk (Библиосфера)
The quality of electronic catalogs is a guarantee of the library collections effective use. However, an adequate methodology for assessing the quality of an electronic catalog (EC) is not available today. It is necessary to introduce a new system of quality analysis. At the research first stage the terminological analysis of the EC notion has been carried out, which reveals the absence of a universal clear definition that allows highlighting an electronic catalog in a series of other similar objects. The author traces main approaches to the definitions formation. These approaches determining allowed us to begin refining the specific characteristics of the electronic catalog based on the professional literature analysis for 1990-2017. The author concludes: the modern EC is a complex multicomponent object, which various components require different criteria and methods of quality analysis. The composition of EC components as quality assessment objects and main evaluating indicators for each component are determined: bibliographical databases (including fullness, data identity and relevance, efficiency, completeness of documents’ identifying characteristics, compliance with the bibliographic description rules, entire and depth of document content reflection, stability of indexing); lexicographic databases (including the information search language (ISL) vocabulary completeness and detail, data identity and relevance, correct wording and alignment of the access points, the compliance with requirements of data presentation formats, ISL grammar tools composition and functionality); factographic data (information completeness and accuracy on the availability and location of publication copies, their movement); database management system and information processing s y st em (functional suitability, accessibility, ease of use, application reliability and security, efficiency, mobility); search system (ISL functionality, ease of navigation in the catalog, efficiency of search techniques and algorithms, relevance criteria, completeness and ease of understanding of search instructions, maintaining the system to help users); user interface (completeness of tasks solved by the system, compliance with human capabilities, visibility and functionality of formats, user-friendly modes of operation with the interface, user feedback, comfort, compliance with aesthetic requirements); system for ensuring the reliability of information storage .